Different scanning protocol to assess left atrial appendage thrombus in patients with atrial fibrillation by cardiovascular computed tomography - Chunjuan Sun; Junwei Lv; Ming Liu; Heng Ma (Scientific Reports)
Abstract To investigate whether we can rule out the left atrial appendage (LAA) thrombus in patients with atrial fibrillation (AF) using different scanning protocol by Cardiovascular Computed Tomography (CCT). We retrospectively reviewed the CCT images of 138 patients with AF to assess LAA thrombus. Patients with no thrombosis diagnosed by preoperative CCT should be confirmed using intraoperative findings as the reference standard. Patients diagnosed with thrombosis were then compared with TEE examination. Different CT scanning protocol were used to assess LAA thrombus according to individual differences. In 126 cases, there was no thrombus in the LAA evaluated by preoperative CCT, and it was confirmed in the subsequent radiofrequency operation. CCT has the accuracy of 100% in confirming the absence of thrombus in the LAA. Twelve thrombi were detected by CCT, eleven thrombi were detected by TEE. Only one patient had different results between CCT and TEE. We could use different CT scanning protocol to rule out LAA thrombus according to individual differences. In some special patients, LAA thrombus can be evaluated by CCT instead of TEE.